TEORI BELAJAR BEHAVIORISME ALBERT BANDURA DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA ARAB - Maulana Maslahul Adi, Habib (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
This research aims to reveal Albert Bandura's theory of behaviorism and its implications in learning Arabic. An in-depth study is needed to dissect Bandura's theory of behaviorism, which is a new figure in the development of learning theories that have been long held by these teachers. This research is a library research, relying on bibliographic sources in the form of books and scientific journals from related research, using descriptive analysis methods to read data and analyze the thinking of Bandura theory. The results of this study indicate that observational learning (modeling), better known as social learning theory and personality psychology, and programs that are based on the concept of stimulus-response, proposed by Bandura, have implications in learning Arabic. The implementations that can be used include: the material presentation of many with ḥiwār, imitation of idioms, habituation, by not teaching qawā'id separately. Then, all learning objectives can be achieved by optimizing the environment of the language (bī'ah).